Who benefits from the corporate QE? A regression discontinuity design approach - Nordine Abidi; Ixart Miquel-Flores (European Central Bank (ECB), 2018)
On March 10, 2016, the European Central Bank (ECB) announced the Corporate Sector Purchase Programme (CSPP) - commonly known as corporate quantitative easing (QE) - to improve the financing conditions of the Eurozone's real economy and strengthen the pass-through of unconventional monetary interventions. Using a regression discontinuity design framework that exploits the rating wedge between the ECB and market participants, we show that: (i) bond yield spreads decline by around 15 basis points at the announcement of the programme, (ii) the impact is mostly noticeable in the sample of CSPP-eligible bonds that are perceived as high yield from the viewpoint of market participants and, (iii) the CSPP seems to have stimulated new issuance of corporate bonds. Overall, our results are consistent with the explanation that highlights the portfolio rebalancing mechanism and the liquidity channel.
Keywords: E50; E52; G11; G30; G32; 330; Unconventional Monetary Policy; Corporate Quantitative Easing (QE); Cost of Financing; Liquidity; Bond Issuance; Regression Discontinuity Design